Emotional Eating dan Riwayat Pemberian Makan Orang Tua sebagai Faktor Risiko Obesitas - Indira Aulia Syafina; Ayu Mutiara Santanu; Delita Septia Rosdiana; Isti Kumalasari (Puslitbang Sinergis Asa Professional, 2026)
Overnutrition remains a problem in Indonesia and even worldwide. It is essentially caused by the imbalance of energy intake and expenditure. Moreover, nutritional status can be influenced by psychosocial factors such as eating behavior and perception of food. Those things can be shaped since childhood influenced by their experience with food such as how parents feed them, and carried it through adulthood. Unhealthy eating behavior, such as emotional eating, is often associated with nutritional status. This research aims to analyze whether parental feeding history and emotional eating are associated with overnutrition in college students in Bandung. The research is a quantitative with a case-control design which was held from February 18-28th 2025 in Bandung with overweight/obese college students as case group and normal-weight college students as control group. Sampling was done using purposive sampling with each group consisting of 47 subjects. Nutritional status was measured by anthropometric measurements, while parental feeding practice history was measured using the Comprehensive Feeding Practices Questionnaire (CFPQ) and emotional eating using the Emotional Eater Questionnaire (EEQ). The data were analyzed using univariate and bivariate (Chi-Square). The result showed that parental feeding practice history (p=0,038; OR=2,616) and emotional eating (p=0,001; OR=4,551) are associated with overnutrition. This finding emphasizes the importance of parental role and emotion regulation in achieving optimal nutritional status.